Evolution of the Auroral Signatures of Jupiter's Magnetospheric Injections. Issue 10 (29th October 2018) - Dumont, M.; Grodent, D.; Radioti, A.; Bonfond, B.; Roussos, E.; Paranicas, C.
Abstract: Auroral emissions equatorward of the main emission at Jupiter are suggested to reflect the dynamics of the plasma in the middle magnetosphere. Here we examine the motion of the auroral signatures of magnetospheric injections appearing in Hubble Space Telescope (HST) images. Our results suggest that the injected plasma moves planetward and lags behind corotation. We then compare the characteristics of the observed signatures with simulations of the auroral precipitation related to injections due to pitch angle scattering. These results indicate that the lifetime of the auroral structures lies between a half and a full rotation of Jupiter. Ultraviolet spectrally resolved images acquired with HST are then used to highlight the energy‐dependent drift of the electrons in auroral injection signatures. Comparison of these observations with simulations of the energy‐dependent drift of injected particles suggests that these structures are ~3‐hr old. Finally, we extend our investigations toward larger and less structured outer emissions possibly associated with younger plasma injections. The motion and evolution of these features are similar to those of the small and compact ones considered in the first part of the study. Key Points: Pitch angle scattering is the most probable auroral mechanism generating auroral signatures of plasma injections at Jupiter The auroral signatures of plasma injection have a lifetime between one half and a full Jovian rotation There is an offset between the maxima in the brightness and color ratio profiles across auroral signature of plasma injections